Biocompatibility Assessment of Polylactic Acid (Pla) and Nanobioglass (N-Bg) Nanocomposites for Biomedical Applications - Zapata-Ramirez, P; Saavedra-Gonzalez, M (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Scaffolds based on biopolymers and nanomaterials with appropriate mechanical properties and high biocompatibility are desirable in tissue engineering. Therefore, polylactic acid (PLA) nanocomposites were prepared with ceramic nanobioglass (PLA/n-BGs) at 5 and 10 wt.%. Bioglass nanoparticles (n-BGs) were prepared using a sol–gel methodology with a size of ca. 24.87 ± 6.26 nm. In addition, they showed the ability to inhibit bacteria such as Escherichia coli (ATCC 11775), Vibrio parahaemolyticus (ATCC 17802), Staphylococcus aureus subsp. aureus (ATCC 55804), and Bacillus cereus (ATCC 13061) at concentrations of 20 w/v%. The analysis of the nanocomposite microstructures exhibited a heterogeneous sponge-like morphology. The mechanical properties showed that the addition of 5 wt.% n-BG increased the elastic modulus of PLA by ca. 91.3% (from 1.49 ± 0.44 to 2.85 ± 0.99 MPa) and influenced the resorption capacity, as shown by histological analyses in biomodels. The incorporation of n-BGs decreased the PLA crystallinity (from 7.1% to 4.98%) and increased the glass transition temperature (Tg) from 53° C to 63° C. In addition, the n-BGs increased the thermal stability due to the nanoparticle’s intercalation between the polymeric chains and the reduction in their movement. The histological implantation of the nanocomposites and the cell viability with HeLa cells higher than 80% demonstrated their biocompatibility character with a greater resorption capacity than PLA. These results show the potential of PLA/n-BGs nanocomposites for biomedical applications, especially for long healing processes such as bone tissue repair and avoiding microbial contamination. © 2022 by the authors. Licensee MDPI, Basel, Switzerland.